Modelling of aerosol trajectories in a mechanically-ventilated study room using computational fluid dynamics in light of the COVID-19 pandemic. (25th April 2022) - Bandara, R.M.P.S.; Fernando, W.C.D.K.; Attalage, R.A.
Millions of people have been infected globally due to the prevailing COVID-19 pandemic and spread of the disease indoors has become a challenging issue. In this context, the study focused on modelling the trajectories of virus-laden aerosols in a study room by the computational fluid dynamics approach under four mechanically-driven ventilation strategies: cavity flow, displacement flow and two cases of mixing flow. Modelling was conducted by coupling discrete phase model with the continuous phase during simulations. Mixing flow - case 1 is proved to be the safest strategy as the virus-laden aerosols leave the room in a single-pass without exposing the occupants. In displacement flow and mixing flow - case 2 ventilation, aerosols get entrapped in the supply air stream, causing heavy circulation while exposing many occupants. The study opens up new avenues for an extensive analysis on establishing an optimal ventilation solution in order to mitigate the spread of COVID-19 indoors.